2020
DOI: 10.1002/app.48955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dual‐crosslinking networks on shape memory performance of polynorbornene

Abstract: In this article, Polynorbornene (PNB)/Zinc dimethacrylate (ZDMA)/Dicumyl peroxide (DCP) composites can form dualcrosslinking networks, which contain an ionic crosslinking network, and a part of the C─C covalent crosslinking network. DCP was used to initiate the polymerization of ZDMA to form ionic crosslinking bonds. With the increase of ZDMA, the total crosslink density (V r ) and ionic crosslink density (V r2 ) increased. DCP was consumed in ZDMA polymerization, which made the PNB reduce the covalent crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…S6 † signies the completion of the thiol-ene click reaction. 26 On the basis of the above results, we deduce that when r Li is below 0.10, the lithium salt rst complexes with oxygen atoms from the ether groups next to azobenzene, and then it begins to complex with oxygen atoms from the ester groups when r Li increases.…”
Section: Resultsmentioning
confidence: 75%
“…S6 † signies the completion of the thiol-ene click reaction. 26 On the basis of the above results, we deduce that when r Li is below 0.10, the lithium salt rst complexes with oxygen atoms from the ether groups next to azobenzene, and then it begins to complex with oxygen atoms from the ester groups when r Li increases.…”
Section: Resultsmentioning
confidence: 75%
“…The measurement of crosslinking density is one of the most efficient methods for revealing structural information on a crosslinked polymer network. The gel content and swelling ratio are usually used to characterize the crosslink density of composite materials [19–21] . In addition, some methods allow one or more reaction groups to be evaluated as a function of time, such as Nuclear magnetic resonance (NMR) spectroscopy, [22–25] attenuation total reflectance Fourier transformation infrared spectrometry (ATR‐FTIR) [26–30] and Raman spectroscopy [31,32] .…”
Section: Introductionmentioning
confidence: 99%
“…The gel content and swelling ratio are usually used to characterize the crosslink density of composite materials. [19][20][21] In addition, some methods allow one or more reaction groups to be evaluated as a function of time, such as Nuclear magnetic resonance (NMR) spectroscopy, [22][23][24][25] attenuation total reflectance Fourier transformation infrared spectrometry (ATR-FTIR) [26][27][28][29][30] and Raman spectroscopy. [31,32] To date, it seems that there is no study demonstrating the impact of the degree of C=C conversion (DC) on dielectric loss.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao [18] introduced dicumyl peroxide (DCP) in PNB to build a cross-linking network in the PNB matrix, which improved the shape recovery ratio of PNB. Gong [19] prepared polynorbornene/zinc dimethacrylate (ZDMA)/dicumyl peroxide (DCP) composites and explored the effect of a double covalent cross-linking network on the shape memory performance of PNB. It was also found that the double crosslinked network stores more energy during deformation, providing a higher ratio of shape recovery.…”
Section: Introductionmentioning
confidence: 99%